2020
DOI: 10.1002/jev2.12036
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin inhibits extracellular vesicle secretion from parasitic nematodes

Abstract: Lymphatic filariasis (LF) is a disease caused by parasitic filarial nematodes that is endemic in 49 countries of the world and affects or threatens over 890 million people. Strategies to control LF rely heavily on mass administration of anthelmintic drugs including ivermectin (IVM), a macrocyclic lactone drug considered an Essential Medicine by the WHO. However, despite its widespread use the therapeutic mode of action of IVM against filarial nematodes is not clear. We have previously reported that filarial ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…Ivermectin is suggested to work via activation of glutamate-gated chloride channels, leading to hyperpolarisation of cell membranes and so paralysis, however ivermectin can also affect other pathways and its mechanism of action is not fully understood ( Laing et al, 2017 ). Effects on EV secretion by ivermectin are seen at far lower concentrations than that needed for motility effects, and closer to the concentrations found after treatment in vivo ( Loghry et al, 2020 ). This suggests that a therapeutic mode of action of ivermectin could involve inhibition of helminth EV secretion, preventing immunomodulation of the host.…”
Section: Helminth Evs and Immunitysupporting
confidence: 68%
See 2 more Smart Citations
“…Ivermectin is suggested to work via activation of glutamate-gated chloride channels, leading to hyperpolarisation of cell membranes and so paralysis, however ivermectin can also affect other pathways and its mechanism of action is not fully understood ( Laing et al, 2017 ). Effects on EV secretion by ivermectin are seen at far lower concentrations than that needed for motility effects, and closer to the concentrations found after treatment in vivo ( Loghry et al, 2020 ). This suggests that a therapeutic mode of action of ivermectin could involve inhibition of helminth EV secretion, preventing immunomodulation of the host.…”
Section: Helminth Evs and Immunitysupporting
confidence: 68%
“…Ivermectin, a drug already used widely to treat helminth infections in both humans and animals, has been found to inhibit EV release in B. malayi, D. immitis and A. suum ( Harischandra et al, 2018 ; Loghry et al, 2020 ). Other anti-helminth drugs, including albendazole and levamisole, do not show inhibition of EV secretion, and no effect of ivermectin was seen on a D. immitis strain that has resistance to the drug, suggesting a specific mode of action for ivermectin ( Loghry et al, 2020 ; Harischandra et al, 2018 ).…”
Section: Helminth Evs and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…When worms were treated with 0.1 µM (Figure 5B) or 1 µM (Supplemental Figure 4) IVM we did not observe any decrease in AgR007_g109_t01: 1908852-1911650 or AgB08X_g209_t01:3249044-3252560 abundance in isolated EVs (Figure 5B, N=3). This observation was perhaps surprising, given the strong and consistent evidence for an inhibitory effect of IVM on EV secretion in parasitic nematodes, including Ascaris (Loghry et al, 2020; Harischandra et al, 2018). This may point to other non-EV mediated routes of circRNA release from these worms.…”
Section: Resultsmentioning
confidence: 99%
“…By playing an important role in both infection and pathology, the secretome of filarial parasites is therefore a promising target for further investigation. Moreover, it has been shown that the anti-filarial drug ivermectin inhibits the excretory-secretory ability of microfilariae, resulting in their death ( Moreno et al., 2010 ; Carithers, 2017 ; Harischandra et al., 2018 ; Loghry et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%